PENGARUH CSR DISCLOSURE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING (STUDI KASUS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR di BEI ) - Wardhani, Rulyanti Susi (Universitas Jember, 2013)
CSR issue influences the corporate business performance, so that the corporate is demanded to be responsive.The aims of the research are to perceive: (1) the influence of CSR disclosure to firm value, (2) the influence of CSR disclosure to the firm value with financial performance as intervening variable. The research took 32 manufacturing companies listed on Indonesia Stock Exchange from 2007 to 2009 for the population by purposive judgement sampling. Data was collected by content analysis and documentation method with the observation period during 3 years. The analysis method used path analysis with SPSS 17 version. The results show that CSR disclosure does not influence the firm value directly, and the firm value with financial performance as variable intervening does not either. Keywords: CSR Disclosure, Firm Value, Financial Performance.